The Role of Change Management Strategies in Preparing Large Organizations in the Globalization Era: Leadership, Communication, Information Technology, and Employee Participation in Business Dynamics - Bakir; Ari Anggarani Winadi Prasetyoning Tyas (Jurnal Minfo Polgan, 2024)
The era of globalization signifies an increase in competition in the global market, with large organizations facing pressure to continuously adapt to rapid and complex changes in the global business environment. Information technology plays a pivotal role in business transformation in the digital era. The development of new technologies and changes in IT infrastructure affect how organizations operate and compete in the global market. The aim of this research is to investigate the influence of change management strategies on the readiness of large organizations in the globalization era. The primary focus of this research is to understand the roles played by four key factors: leadership, communication, information technology, and employee participation in addressing business dynamics in the globalization era. This research method involves a literature review with a qualitative approach and descriptive analysis. The literature review was conducted by gathering, reviewing, and synthesizing relevant scholarly articles found through searches on Google Scholar within the timeframe of 2001-2024. The study results indicate that in the ever-changing and evolving era of globalization, large organizations must be prepared to adapt quickly to remain relevant and competitive. The implementation of change management strategies is crucial in ensuring organizational readiness to face modern business dynamics. The influence of these strategies is highly significant and involves various factors such as leadership, communication, information technology, and employee participation. Strong leadership, effective communication, leveraging advanced information technology, and high employee participation are essential elements of these strategies. Therefore, one of the recommendations that can be drawn from this research is that organizations should focus on developing strong and visionary leadership to inspire and guide the organization through the change process.